MENINGKATKAN KEMAMPUAN MENGENAL BENTUK GEOMETRI ANAK USIA 3-4 TAHUN MELALUI PERMAINAN KOTAK POS GEOMETRI DI KB TUNAS BANGSA KECAMATAN TAPUNG KABUPATEN KAMPAR - Fitriyah '; Tri Umari; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study was to investigate the application of post box games geometry to improve the ability to know the geometry of children aged 3-4 years, know how to improve the ability to know the geometry of children aged 3-4 years through a post office box games geometry. The research was conducted in the second semester of 2015/2016 academic year in April-May 2016 in KB Tunas Bangsa Tapung District of Kampar regency. This type of research is on classroom action research. The subject of this research consisted of 16 children, consisting of 6 girls and 10 boys with children ages 3-4 years. Based on the results of this research note that, (1) The application of post box games geometry can improve the ability to know the geometry of children aged 3-4 years (2) How to improve the ability to know the geometry of children aged 3-4 years that is by using action research in two cycle, as in the first cycle there are three meetings so overall game geometry applied postbox 6 meetings. Based on research that has been carried out it turned out action research to improve the ability of children aged 3-4 years in the familiar form of geometry through the game mailbox by obtaining the results of the pre cycle to cycle I is 24.47%, the first cycle to the second cycle of 51.86% and from the pre cycle to cycle II of 89.03%.